Predicting Marital Commitment Based on Differentiation in Women: With the Mediating Role of Emotional Intelligence - Fardad, Farokh; Dokaneifard, Farideh; Mirhashemi, Malek (Psychology of Woman Journal, 2021)
The research aimed to determine the structural model of predicting marital commitment based on differentiation in women with the mediating role of emotional intelligence. The research method was a correlation, and the statistical population was all married women referring to counseling centers in Tehran in 2018. In this way, random sampling was used to select counseling centers. For this purpose, the city of Tehran was divided into five regions: North, South, East, West, and Center. Then, three counseling centers were randomly selected from each region, and 300 women were selected based on Sample Power software. Then Adams and Jones’ (1997) Marital Commitment Questionnaire, Skowron and Friedlander’s (1998) Differentiation Questionnaire, and Bar-Ann Emotional Intelligence Questionnaire (2002) were completed, and the data were analyzed using Smart Plus structural equations. The results showed at the 99% confidence level that the structural model can predict marital commitment based on differentiation with the mediation of emotional intelligence (β=0.120) and has a good fit. The direct path of differentiation (β-0.39) and emotional intelligence (β-0.28) on marital commitment was significant and the indirect path showed that differentiation with the mediation of emotional intelligence had a favorable effect on marital commitment. For the cohesion and creation of a desirable marital relationship, it is possible to improve the differentiation by strengthening the emotional intelligence of each couple.